2020
DOI: 10.1016/j.physleta.2019.126177
|View full text |Cite
|
Sign up to set email alerts
|

Topological modes in radiofrequency resonator arrays

Abstract: Topological properties of solid states have sparked considerable recent interest due to their importance in the physics of lattices with a non-trivial basis and their potential in the design of novel materials. Here we describe an experimental and an accompanying numerical toolbox to create and analyze topological states in coupled radiofrequency resonator arrays. The arrays are coupled harmonic oscillator systems that are very easily constructed, offer a variety of geometric configurations, and whose eigenfun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This robust phenomenon was confirmed experimentally not long ago with ultra-cold fermionic and bosonic atoms [4,5], even though the prediction was made forty years ago. Since then, the phenomenon has received renewed attention from the meta-material community because of the possibility of resonant spectrum engineering [6][7][8][9][10][11], of topological wave-steering [12][13][14][15][16][17][18][19][20], as well as of dynamic edge-to-edge pumping [21][22][23][24]. The last batch of experimental achievements are highly relevant for the present work, because they demonstrated that fast dynamic re-configurations of the meta-materials are now possible, to a level where the pumped signals do not succumb to dissipation and the effect can be revealed.…”
mentioning
confidence: 99%
“…This robust phenomenon was confirmed experimentally not long ago with ultra-cold fermionic and bosonic atoms [4,5], even though the prediction was made forty years ago. Since then, the phenomenon has received renewed attention from the meta-material community because of the possibility of resonant spectrum engineering [6][7][8][9][10][11], of topological wave-steering [12][13][14][15][16][17][18][19][20], as well as of dynamic edge-to-edge pumping [21][22][23][24]. The last batch of experimental achievements are highly relevant for the present work, because they demonstrated that fast dynamic re-configurations of the meta-materials are now possible, to a level where the pumped signals do not succumb to dissipation and the effect can be revealed.…”
mentioning
confidence: 99%
“…(2) (Non-Hermitian case) A dimeric array with alternating capacitances, C 1 = C 3 = C 5 , corresponding to a frequency of f = 200 MHz, and C 2 = C 4 corresponding to f = 220 MHz. Such a dimeric array exhibits a band gap that is evident with five elements but evolves more fully in the asymptotic limit of infinite N [18].…”
mentioning
confidence: 99%
“…In the experiment, the resonator arrays were composed of N = 5 rectangular LC loops that were aligned coaxially and have been described in detail previously [18]. Individual resonators were tuned by a trim capacitor to their base frequencies, which are defined as the resonance frequencies of the isolated uncoupled elements.…”
mentioning
confidence: 99%
See 2 more Smart Citations